Reconstruction, replication and re-enactment in the humanities and social sciences - Stols-Witlox, Maartje; Kursell, Julia; Lulof, Patricia S.; Harris, Anna; Dupré, Sven, 1975- (Amsterdam University Press, 2020)
Performative methods are playing an increasingly prominent role in research into historical production processes, materials, bodily knowledge and sensory skills, and in forms of education and public engagement in classrooms and museums. This book offers, for the first time, sustained, interdisciplinary reflections on performative methods, variously known as Reconstruction, Replication and Re-enactment (RRR) practices across the fields of history of science, archaeology, art history, conservation, musicology and anthropology. Each of these fields has distinct histories, approaches, tools and research questions. Researchers in the historical disciplines have used reconstructions to learn about the materials and practices of the past, while anthropologists and ethnographers have more often studied the re-enactments themselves, participating in these performances as engaged observers. In this book, authors bring their experiences of RRR practices within their discipline into conversation with RRR practices in other disciplines, providing a basis for interdisciplinary cross-fertilization.